Exploring External Load Metrics in Team Handball: A Study of Europe's Under-20 Male Championship - João Freitas; Luisa Estriga (Federación Extremeña de Balonmano; University of Extremadura, 2024)
The objective assessment of external physical loads has become promising in better understanding players' match loads and responses. However, there is a lack of consensus on the metrics used along with limited information on this topic in elite handball. This study investigated differences in conventional and novel external load metrics according to playing positions. Methods: 27 matches of EHF Euro M20 2022 were used, with a total of 711 player match observations recorded. The data series were collected using a local positioning system (LPS) integrated with inertial measurement unit (IMU) devices. Kinematic variables: match-jerk, match-Dynamic Stress Load (match-DSL), distance covered, distance covered at high speed (HSR distance). Despite the lack of handball-specific validation, differences between studied positions were found in all variables. Greater sensibility seems possible based on the match-DSL compared to match-jerk. Accordingly, Backs exhibited the highest match-DSL values. Divergently, the Wings covered more distance at total and high-speed running while showing lower match-DSL relative to the Backs. The Line Players had similar HSR distances to Backs while covering lower total distances. Future studies are needed to explore the validity of the available metrics and arbitrary parameters, as well as comparing those variables with internal-load variables.